Optimization of hang-time technique for volleyball spike jumps - Gupta, D.; Neptun, R. R.; Jensen, J.; Abraham, L. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
In a previous study, we found that hang-time can have potential benefits on athlete performance during volleyball spikes, but hang-time usually comes at a cost of decreased peak height. To address this loss in peak height, we tested whether the trajectories of the "non-performing segments" (legs and non-hitting arm) can be modified to maximize the performance of the hitting arm without affecting the hang-time (defined by vertical motion of the head and trunk). The purpose of this study was to present details of an optimizer to facilitate a wide range of future studies aimed at maximizing performance. Using optimization we predict that for males the peak height of the hitting arm and its sagittal plane velocity at its peak can be increased by 52k11 mm (p<0.001) and 3.0fl.6 mls (p< 0.001) by modifying the trajectories of the non-hitting and hitting side legs respectively.